Back to basics: exploring perceptions of stakeholders within the Swedish fashion industry. Issue 2 (5th June 2017) - Pedersen, Esben Rahbek Gjerdrum; Lauesen, Linne Marie; Kourula, Arno
Abstract : Purpose: The purpose of this paper is to examine to what extent the conventional stakeholder model mirrors managerial perceptions of the stakeholder environment in the Swedish fashion industry. The authors aim to adopt a novel approach to stakeholder measurement, as the traditional stakeholder model is constrained by its static two-dimensional nature, which captures neither the nuances of the stakeholder literature nor the dynamics of the firm's stakeholder universe. Design/methodology/approach: Empirically, the paper is based on findings from a survey among 492 Swedish fashion manufacturers and retailers. Findings: The paper reports significant discrepancy between the conventional stakeholder model and the perceptions of real-life managers of the stakeholder environment. On the surface, their understanding is more in line with the managerial model of the firm from which the stakeholder literature originally departs. It is argued, however, that the discrepancy may be rooted in technology rather than theory as the stakeholder model is constrained by its static two-dimensional nature, which captures neither the nuances of the stakeholder literature nor the dynamics of the firm's stakeholder universe. The paper, therefore, introduces an animated alternative to the conventional stakeholder model that provides a richer graphical representation of a firm's stakeholder universe. Research limitations/implications: The paper refers to the open-ended questions in the survey in terms of descriptive statistics, and not the entire quantitative measures in the survey. This is because these questions are crucial to the authors' approach to the suggested new stakeholder model, which is not tested quantitatively, but should be perceived as explorative – as a qualitative outcome of the survey. The survey is conducted through the web in the Swedish fashion industry only; thus; the authors' suggested model needs further quantitative qualification, which the authors plead for in future research. Originality/value: The originality of the paper is its novel approach to stakeholder measurement based on the perceptions of real-life managers of the stakeholder environment of the Swedish fashion industry. The traditional stakeholder model is constrained by its static two-dimensional nature, which the paper's animated three-dimensional alternative provides a richer graphical representation of a firm's stakeholder universe.